2005
DOI: 10.21273/hortsci.40.1.102
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Calcium Application Influences Potato Tuber Number and Size

Abstract: Tuberization in potato is known to be under complex biochemical control involving hormones. A number of studies have provided evidence for a critical role of GA in tuberization. There is also evidence that GA in plants can be modulated by a Ca/calmodulin pathway. The purpose of the present study was to determine the influence of supplemental Ca fertilization on tuber size and tuber number. Plantlets of Solanum tuberosum `Russet Burbank' raised in tissue culture were planted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
6
13
0
Order By: Relevance
“…We have evidences supporting the idea that the impact of environmental stresses on potatoes can be reduced by improving calcium nutrition (Palta 1996;Tawfik et al 1996;Vega et al 1996;Kleinhenz and Palta 2002). Furthermore, our studies also suggest that Ca can modulate hormone type of responses in potatoes such as influencing the tuberization signal (Ozgen et al 2003;Ozgen and Palta 2004;Vega et al 2006). …”
Section: Introductionsupporting
confidence: 83%
“…We have evidences supporting the idea that the impact of environmental stresses on potatoes can be reduced by improving calcium nutrition (Palta 1996;Tawfik et al 1996;Vega et al 1996;Kleinhenz and Palta 2002). Furthermore, our studies also suggest that Ca can modulate hormone type of responses in potatoes such as influencing the tuberization signal (Ozgen et al 2003;Ozgen and Palta 2004;Vega et al 2006). …”
Section: Introductionsupporting
confidence: 83%
“…In a greenhouse experiment, Ozgen and Palta (2005) found that Ca application decreased the number of tubers per plant. Total yield was not affected by Ca, but the decrease in tuber number was accompanied by an increase in tuber size.…”
Section: Treatment Effects In 2002 and 2003 On Tuber Numbersmentioning
confidence: 99%
“…This proved that calcium signaling pathway is dominant in the tuberization and further growth (Upadhyaya et al, 2013). It is established fact that the Ca 2+ is a second messenger in several plant signaling pathways, adding extracellular stimuli to intracellular and whole-plant responses (Ozgen et al, 2005). Concentration of cellular Ca 2+ is tightly regulated, and a little variation in its concentration changes the signaling and protein activation.…”
Section: Discussionmentioning
confidence: 99%
“…A few other studies demonstrated the influence of supplemental Ca2+ on tuberization of potato under field conditions (Ozgen et al, 2000(Ozgen et al, , 2003(Ozgen et al, , 2006Ozgen and Palta, 2004;Chang et al, 2007) though the exact molecular mechanism of its influence was not studied. Present study was undertaken to investigate the biochemical and molecular mechanism underlying tuberization in potato influenced by Ca 2+ supplementation under in vitro conditions.…”
Section: Introductionmentioning
confidence: 99%